Early-Onset Neonatal Sepsis and Respiratory Distress in a Newborn with Congenital Diaphragmatic Hernia: A Case Report - Nasution, Uji Kuatro; Suwardi (HM Publisher, 2024)
Background: A congenital diaphragmatic hernia (CDH) is a severe birth defect where abdominal organs protrude into the chest cavity through a hole in the diaphragm, often leading to respiratory distress. Neonates with CDH are also at an increased risk of developing early-onset neonatal sepsis (EOS) due to impaired lung development and immune function. This case report describes the challenges in managing a newborn with CDH who developed EOS and respiratory distress shortly after birth. Case presentation: A 2-day-old infant presented with respiratory distress, including tachypnea, grunting, and retractions. The infant was born full-term via cesarean section with Apgar scores of 5, 7, and 8 at 1, 5, and 10 minutes, respectively. Physical examination revealed decreased breath sounds, dullness to percussion, and decreased fremitus on the left side of the chest. A chest X-ray showed intestinal gas in the left thoracic cavity, confirming the diagnosis of CDH. Laboratory investigations revealed anemia, thrombocytopenia, neutrophilia, lymphocytopenia, and hypocalcemia, suggesting EOS. The infant was admitted to the neonatal high care unit (HCU) and received respiratory support with continuous positive airway pressure (CPAP) and was kept nil per os (NPO). A laparotomy was planned to repair the diaphragmatic hernia. On day 3, the infant developed signs of sepsis and was started on antibiotics. After stabilization, the infant was transferred to the neonatal intensive care unit (NICU) for definitive surgical repair. Post-operatively, the infant received antibiotics, analgesics, and supportive care. Conclusion: This case highlights the complexities of managing newborns with CDH and EOS. Early recognition and prompt intervention are crucial for improving outcomes in these critically ill infants.